P.027 Investigation of hippocampal sub-structures in HS and non-HS focal temporal lobe epilepsy at 7T. (17th June 2016) - Santyr, BG; Goubran, M; Lau, J; Kwan, B; Mirsattari, SM; Burneo, JG; de Ribaupierre, S; Hammond, RR; Peters, TM; Khan, AR
Abstract : Background: The clinical identification of hippocampal sclerosis (HS) is important in predicting surgical outcomes in patients with temporal lobe epilepsy (TLE). In cases where gross hippocampal sclerosis is not identifiable clinically, a more detailed analysis of hippocampal subfields using ultra-high-field magnetic resonance imaging (MRI) may reveal areas of abnormality, which was the focus of our study. Methods: Patients (N=13) with drug-resistant TLE (9 no-HS, 4 HS) and 20 age-matched healthy controls were scanned and compared using a 7T MRI protocol. Using a manual segmentation scheme to delineate hippocampal subfields, subfield-specific volume changes were studied between the two groups. In addition, radiological patient assessment at 7T was correlated with measured subfield changes. Results: Volumetry of the hippocampus at 7T in HS patients revealed significant ipsilateral subfield losses in CA1 and CA4DG. Volumetry also uncovered subfield volume losses in 33% of no-HS patients, which had not been detected conventionally. Furthermore, 89% of no-HS patients showed abnormality (internal architecture or size) at 7T, identified by radiologists blinded to the patient's initial classification. Conclusions: These preliminary findings indicate that hippocampal subfield volumetry assessed at 7T may be superior to conventional visual inspection by a neuroradiologist in the identification of hippocampal pathologies in TLE.